2018
DOI: 10.2147/cia.s174000
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in microRNAs and ischemic stroke in an Asian population: evidence based on 6,083 cases and 7,248 controls

Abstract: BackgroundPolymorphisms in miR-146a (rs2910164), miR-196a2 (rs11614913), miR-149 (rs2292832) and miR-499 (rs3746444) have been associated with ischemic stroke (IS), but studies have given inconsistent results.MethodsThis meta-analysis investigated the possible association between IS risk and the four polymorphisms. A total of 14 case-control studies from Asian populations involving 6,083 cases and 7,248 controls for the four polymorphisms were included.ResultsResults showed that the GG genotype of miR-146a (rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…In a previous review article, Zou et al (21) concluded that the miR-499 (rs3746444) polymorphism may not be associated with a risk of IS in Asian populations. However, in the present study, neither the allelic model, dominant model, recessive model, homozygote model, or the heterozygote model were found to be significant in the study by Zou et al However, as 3 Chinese articles were included in the review article by Zou et al (21), it is difficult for researchers who do not speak Chinese to repeat the results.…”
Section: Discussioncontrasting
confidence: 76%
“…In a previous review article, Zou et al (21) concluded that the miR-499 (rs3746444) polymorphism may not be associated with a risk of IS in Asian populations. However, in the present study, neither the allelic model, dominant model, recessive model, homozygote model, or the heterozygote model were found to be significant in the study by Zou et al However, as 3 Chinese articles were included in the review article by Zou et al (21), it is difficult for researchers who do not speak Chinese to repeat the results.…”
Section: Discussioncontrasting
confidence: 76%
“…The direct regulatory effects and predicted targeting effects against ACE and PAI-1, mediated by miR-10a, miR-27a, miR-34b/c, and miR-300, have been described by previous studies [43][44][45][46]66]. Moreover, we have already reported the association between another miRNA and ischemic stroke, and many studies in another population demonstrated the association between other miRNAs and ischemic stroke [78][79][80][81].…”
Section: Discussionsupporting
confidence: 70%
“…Ischemic stroke is thought to occur when cerebral artery stenosis and reduction or interruption of regional cerebral blood flow decrease the supply of oxygen and energy to brain tissue, triggering secondary vascular endothelial damage and autonomic nervous dysfunction. 4,5 Cellular and animal models and postmortem studies indicate that ischemic stroke involves oxidative stress, apoptosis, calcium overload, mitochondrial dysfunction, inflammatory and immune responses, as well as changes in microRNA levels. [6][7][8][9] Mitochondrial dysfunction appears to contribute to ischemic stroke by increasing oxidative stress, perturbing calcium homeostasis and inducing neuronal apoptosis.…”
Section: Introductionmentioning
confidence: 99%